The Utilization of Google Workspace in Economics Learning SMAN 68 Jakarta - Hidayah, Shofiyatul; Wibowo, Agus; Saparuddin, Saparuddin (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
This study aims to describe student engagement in post-pandemic face-to-face learning in economics lessons at SMAN 68 Jakarta. This study also aims to describe learning innovations designed by teachers by utilizing existing features in Google Workspace. Finally, this study presents recommendations for using Google Workspace for economic learning to increase student engagement. This study uses qualitative descriptive methods and research samples of economics teachers of SMAN 68 Jakarta. The method of data collection carried out is observation and interview. The data analysis method used is qualitative descriptive analysis. The results indicate no shortage of student involvement in face-to-face learning in economics lessons. Teachers have taken advantage of the features in Google Workspace but haven't made the most of them. Teachers can use Google Docs and Google Slides for economics learning so that student engagement can increase significantly. This feature requires students to actively collaborate to complete assignments because teachers can monitor in real time the activities carried out by students.